RANKL confers protection against cell death in precision-cut lung slices - Ruigrok, M. J. R.; Roest, M. A. P.; Frijlink, H. W.; Olinga, P.; Hinrichs, W. L. J.; Melgert, B. N. (Frontiers in Physiology, 2022)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death globally and constitutes a major health problem. The disease is characterized by airflow obstructions due to chronic bronchitis and/or emphysema. Emerging evidence suggests that COPD is the result of impaired epithelial repair. Motivated by the need for more effective treatments, we studied whether receptor activator of nuclear factor κ-Β ligand (RANKL) contributed to epithelial repair, as this protein has been implicated in epithelial regeneration of breast and thymus. To do so, we used precision-cut lung slices prepared from mouse tissue—viable explants that can be cultured ex vivo for up to a few days while retaining features of lung tissue. Slices were cultured with 10, 100, or 500 ng/mL of mouse RANKL for 24 h. We first found RANKL activated nuclear factor κ-Β signaling, which is involved in cellular stress responses, without affecting the general viability of slices. Cell proliferation, however, was not altered by RANKL treatment. Interestingly, RANKL did reduce cell death, as revealed by TUNEL stainings and profiling of apoptosis-related proteins, indicating that it contributes to repair by conferring protection against cell death. This study improves our understanding of lung repair and could create new opportunities for developing COPD treatments.